Upaya Pemulihan Ekonomi Pasca Pandemi Covid-19 di Desa Wisata Lor Sambi, Yogyakarta - Annisa Mu'awanah Sukmawati; Farrel Dhaniswara (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2022)
The Covid-19 pandemic has had a major impact on many sectors, not only health but also tourism. The dynamics of government policies in line with the fluctuations in the number of Covid-19 events have had their own impact on the development of the tourism industry; one of them is tourist villages. During the pandemic, tourist villages are one of the government's priorities to restore the tourism sector because tourist villages have a broad impact on the community's economic recovery. Lor Sambi Tourism Village is one of the tourist villages affected by the pandemic. The decrease or even the absence of the number of visits affects tourism income and has an impact on the financial needs needed for the operation of tourist villages. This study aims to demonstrate the efforts to restore the tourism economy after the Covid-19 pandemic in the Lor Sambi Tourism Village, Sleman Regency. The research used qualitative research methods. Data was collected by interviewing four informants using the purposive sampling technique and direct field observations of tourist villages. Research showed that the Covid-19 pandemic has both negative and positive impacts on the Lor Sambi Tourism Village. The negative impact is in the form of a decrease in tourism revenue due to a decrease in visitors. Meanwhile, the positive impact is that tourism object managers can find new tourist attractions to attract visitors' interest and revamp the tourist village to comply with health protocol standards. Changing tourism trends into technology-based tourism in terms of product marketing and tourism management needs to be considered, and also needs to be supported by collaboration with other parties, such as the private sector and the government.